Study of a V-shape flame based on IR spectroscopy and IR imaging. (January 2016) - Pouplin, J.; Collin, A.; Acem, Z.; Parent, G.; Boulet, P.; Vena, P.; Galizzi, C.; Kühni, M.; André, F.; Escudié, D.
Abstract: Applicability of an IR imaging/spectroscopy diagnostic was tested on a laboratory- scale flame. For this purpose, measurements were carried out on a V-shape flame developed along a wall, with the aim of evaluating the wall temperature and of identifying the flame properties (temperature and species concentrations). Infrared measurements with a multiband camera and a spectrometer were post-processed and compared, in particular, with thermocouple measurements carried out for the wall temperature. Simple evaluation involving a correction for the emissivity showed a quite good agreement when assessed against experimental data. An attempt to reconstruct a flame emission spectrum was also carried out, expecting a possible inverse identification of the flame properties. The method showed a promising behaviour on synthetic data built with a radiative transfer model for gas and wall radiation. However, the spectrum reconstruction method is not yet accurate enough to allow an identification of the flame properties in full confidence when applied to actual experimental data. First tests showed a correct qualitative behaviour, but model refinements are required at least for the flame radiation, before getting accurate flame properties.